Drug therapy for bipolar disorder: A review of efficacy evidence - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2023)
The purpose of this article is to provide scientific evidence on mood stabilizers used in the treatment of bipolar disorder. Indeed, it has proven difficult to develop drugs for this disorder, particularly in long-term treatment for relapse prevention. We review the main drugs that have obtained approval for use in the European Union and the United States. We take again the clinical studies which provided the basis for the evaluations. These studies are few in number and relatively old as it is difficult to conduct them in bipolar disorder. These are studies in monotherapy but also in dual therapy which better reflects the daily use of these drugs.